Influence of Male to Female Ratio on Hormone Profiles and Reproductive Performance of Anestrus Postpartum Ewes Subjected to the Male Effect - Ferreira-Silva, José Carlos; Burnett, Tracy Anne; Souto, Paulo Francisco Maciel Póvoas; Rocha, Jorge Motta; Ferreira, Heder Nunes; Moura, Marcelo Tigre; Caldas, Eduardo Luiz Cavalcanti; Oliveira, Marcos Antonio Lemos (Acta Scientiae Veterinariae, 2017)
Background: Complete isolation of genders allows intense estrous induction and synchronization once rams are introduced in ewe flocks at the onset of the breeding season (BS). This management practice, defined as the male effect, results from a neuroendocrine process mediated by pheromones. The male effect is a straightforward procedure to induce estrous in noncycling ewes, but conditions for its use have not been fully explored. Thus, this study aimed to evaluate hormone levels and ovarian activity of postpartum ewes in anestrus which are subjected to the male effect under different male to female ratios. Material, Methods & Results: Pospartum females were selected according to body condition score and cyclicity status. Females were kept apart from males during 30 days at a distance of 10 m. Anestrus and ovulation were determined by P4 measures on days 10, 20 and 30 after isolation from males. After P4 concentration diagnosis, anestrus ewe (n = 99) were subjected to male to ewe ratios (MFR) of 1:20 (MFR20), 1:30 (MFR30) and 1:40 (MFR40). Santa Inês rams (n = 3) of proven fertility were used. Three females of each group were randomly subjected to blood collection for LH concentration analysis. Ovarian activity was performed by ultrasonography after estrus manifestation in six ewe of each group. Estrus events were observed twice a day during the BS of 35 days, and estrus were considered synchronized when it occured within the initial five days of the BS. Pregnancy diagnosis was performed by ultrasonography on days 35 and 60 after the last mating. All ewe were in a non-cycling condition before BS onset, based upon P4 analysis. After initiation of the BS, P4 concentrations increased for all groups. Irrespectively of male to female ratio, male effect induced LH pre-ovulatory peaks within the initial 26 to 86 h of the BS. Synchronization of estrus reached 50% for MFR20, 40% for MFR30 and 20% for MFR40 for all ewe. Moreover, overall estrus incidence was 100% (MFR20), 90% (MFR30) and 65% (MFR40) within the initial 15 days of the BS. However, incidence of ewe that had repeated estrus events was lower for MFR20 than for MFR30. Follicular growth and number of ovulations was similar between groups. Conception rates on first service was higher than that of second service for MFR20 and MFR30, although there was no difference between services for MFR40. In contrast, overall conception rates, delivery type and prolificacy were similar between groups. Discussion: P4 increased to cyclicity levels after contact between genders, demonstrating the potential of the male effect to induce estrus in non-cycling ewes. Most ewe ovulated within three days after the male effect, possibly due to elevated basal LH levels. Moreover, the LH preovulatory peak varied within groups, possibly due to greater interactions between genders, which ultimately may have led to earlier ovulation anticipation under lower MFR. Estrus parameters were similar between groups, suggesting low or negligible effects of MFR. Ovulatory follicle size and growth and the number of ovulations were similar between all groups; previous reports have suggested that this may be due to a strong effect of their genetic background. Conception rates were higher at first than second services, demonstrating the potential of male effect. In conclusion, male to female ratio affects the efficiency of the male effect to induce and synchronize estrus in ewes under postpartum anestrus, but it does not affect conception rates and prolificacy.